История создания, становления и развития Украинского степного природного заповедника НАН Украины и его отделений за 75 лет - Генов, А.П.; Ткаченко, В.С.; Генова, Л.Ф. (Промышленная ботаника, 2002)
The information of archives and from literary sources on the history of foundation, formation and development of the Ukrainian steppe natural reserve, Nat.Acad.Sci. of Ukraine and its subdivisions for 75 years are cited. The issues of the present state, studying and protection of the reservation areas are addressed.